2017
DOI: 10.1080/01635581.2017.1359313
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Endometrial Cancer: A Lack of Knowledge but Opportunity for Intervention

Abstract: Objective: The causal link between obesity and endometrial cancer is well-established, however obese women’s knowledge of this relationship is unknown. Our objective was to explore patients’ understanding of this relationship and assess the acceptability of a technology-based weight loss intervention. Methods/Materials: Obese women with Type I endometrial cancer/hyperplasia were surveyed about their assessment of their body mass, knowledge of the relationship of obesity and endometrial cancer, and eating and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 16 publications
(20 reference statements)
4
23
0
Order By: Relevance
“…The question of weight loss is relevant as Haggerty and colleagues pointed out in 2017. They conducted a survey among patients with stage I EC and found that 59% of the patients reported great interest in using weight loss as a preventive method against recurrence [ 3 ].…”
Section: Weight Reduction and Its Value As Prevention Measurementioning
confidence: 99%
See 2 more Smart Citations
“…The question of weight loss is relevant as Haggerty and colleagues pointed out in 2017. They conducted a survey among patients with stage I EC and found that 59% of the patients reported great interest in using weight loss as a preventive method against recurrence [ 3 ].…”
Section: Weight Reduction and Its Value As Prevention Measurementioning
confidence: 99%
“…Increasing body mass index (BMI) is a phenomenon being seen not only in the classical Western world but also in developing countries [ 1 , 2 ]. Indeed, one-third of American women are obese, defined by a BMI > 30 kg/m 2 , with about 7% presenting with severe or morbid obesity (BMI > 40 kg/m 2 ) [ 3 ]. There is a strong, well-established association between obesity and the development of endometrial cancer (EC) [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the pathogenesis and biological behavioral characteristics, UCEC can be divided into estrogen-dependent type (type I) and non-estrogen-dependent type (type II) (4). Approximately 40% of cases are related to obesity (5,6). Besides, endometrial cancer is also associated with excessive estrogen exposure, hypertension, and diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity has been shown repeatedly to be one of the strongest EC risk factors that drives all-cause and cancer-specific mortality (Gunderson et al, 2014; Arem et al, 2013; von Gruenigen et al, 2006). Appropriately, an abundance of research has been dedicated to better understanding patients' knowledge of the impact of obesity on cancer, and multi-centered weight loss interventions have been implemented among EC survivors to help reduce their risk of death (Ackermann et al, 2005; Connor et al, 2017; Haggerty et al, 2017a, Haggerty et al, 2017b; Kuroki et al, 2015; Soliman et al, 2008). Unfortunately, positive outcomes of weight loss interventions are brief and reach only a small subset of women affected with EC (Haggerty et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%